Pengembangan Model Pembelajaran Ilmu Komputer Berbasis Riset Otak untuk Meningkatkan Hasil Belajar Mahasiswa PTIK Universitas Dehasen Kota Bengkulu - Siska, Jumiati; Selviani, Diah; Yul, Fadlul Amdhi (Sinkron : jurnal dan penelitian teknik informatika, 2017)
This study aimed to generate a learning model of Computer Science based on brain research to improve learning outcomes of PTIK students of Dehasen University Bengkulu. Type of this research was a development study that generates a brain-based learning model. The syntaxes were a) introduction; b) coreactivities, including (i) problem-giving phase, (ii) investigation phase, (iii) group discussion phase, (iv) class discussion phase, (v) application phase; c) closing. The development design according to Plomp (in Wahyu Widada: 2012), consists of five phases, namely: initial investigation; design; construction (realization); test, evaluation and revision; and implementation. The subjects of this study were students of PTIK Dehasen University of Bengkulu City academic year 2016/2017.Based on the results of the study and from the test that had been conducted once―which was a limited test, it can be concluded that: all aspects used to state that the learning model and all learning devices developed are practical and effective had been fulfilled, then the development cycle to get a practical and effective learning model has ended.But even if all the criteria were met, some revisions needed to do to get the final Prototype. The revisions were related to the use of language in the model book and student activity sheets. After the revisions were done, the final prototype was obtained, which is a valid, practical, and effective Mathematical Learning Model based on brain research.